Qiancao (Rubia spp.) – a comprehensive metabolomics analysis of the five core species - Zhang, Mingtong; Du, Junyan; Li, Donghua; Ma, Xiao; Jin, Wanjun; Xiang, Lei; Wen, Meng (Frontiers in Pharmacology, 2025)
IntroductionQiancao comprises five closely related species: Rubia cordifolia L., Rubia yunnanensis Diels., Rubia wallichiana Decne., Rubia schumanniana Pritz., and Rubia magna P. G. Xiao. Due to their similar morphological characteristics, alternative species are frequently substituted for R. cordifolia L. in traditional medicine. However, the latest National Pharmacopoeia of China only exclusively recognizes R. cordifolia L. as the official medicinal source. The metabolic differences among these species remain poorly characterized, largely owing to the absence of systematic metabolomic studies.MethodsThis study employed a metabolomics approach to investigate the five Rubia species. The selected species were analyzed using an untargeted metabolomic approach based on ultrahigh-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS). Subsequently, multivariate statistical analysis combined with bioinformatics was applied to identify differential metabolites and elucidate their associated metabolic pathways.Results and discussionThis metabolomics analysis identified a total of 1,440 metabolites. Comparative analyses revealed significant differences in the metabolic profiles among the five species. Specifically, we detected 237, 217, 448, and 226 differentially accumulated metabolites when comparing R. cordifolia L. with R. magna P. G. Xiao, R. cordifolia L. with R. schumanniana Pritz., R. cordifolia L. with R. yunnanensis Diels., and R. cordifolia L. with R. wallichiana Decne., respectively. KEGG pathway analysis demonstrated substantial involvement of these metabolites in three key pathways: amino acid metabolism, riboflavin metabolism, and terpenoid biosynthesis, with particular emphasis on specific metabolites within these pathways. These findings provide a foundation for future research focused on species identification, quality control, biosynthetic pathway investigation, and bioactivity assessment of Qiancao, thereby advancing the understanding of its clinical applications in traditional Chinese medicine.